Ericoid mycorrhizal fungi as biostimulants for improving propagation and production of ericaceous plants - Wei, Xiangying; Zhang, Wenbing; Zulfiqar, Faisal; Zhang, Chunying; Chen, Jianjun (Frontiers in Plant Science, 2022)
The mutualistic association of plant roots with mycorrhizal fungi is one of the most widespread terrestrial symbioses. The symbiosis enables plants to better adapt to different soil conditions and improve their establishment and growth. Thus, mycorrhizal fungi are considered as biostimulants in promoting plant growth and alleviating plant abiotic and biotic stresses. Among them, arbuscular mycorrhiza and ectomycorrhiza fungi have been more extensively studied than ericoid mycorrhiza (ErM) and orchidaceous mycorrhiza fungi. ErM fungi can form symbiotic relationships with plants in the family Ericaceae. Economically important plants in this family include blueberry, bilberry, cranberry, and rhododendron. ErM fungi are versatile as they are both saprotrophic and biotrophic. Increasing reports have shown that they can degrade soil organic matter, resulting in the bioavailability of nutrients for plants and microbes. ErM fungi can synthesize hormones to improve fungal establishment and plant root initiation and growth. ErM colonization enables plants to effective acquisition of mineral nutrients. Colonized plants are able to tolerate different abiotic stresses, including heavy metals, salt, and drought and biotic stresses, such as pathogens. This article is intended to briefly introduce ErM fungi and document their beneficial effects on ericaceous plants. It is anticipated that the exploration of this special group of fungi will further improve our understanding of the value of symbiosis to ericaceous plants and ultimately result in the application of valuable species or strains for improving the establishment and growth of ericaceous plants.